Eco Taxation as Instrument of Eco Economy Regulation. (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The main target of this article is to determine the role of eco tax in the structure of GDP formation, and the importance of eco taxation for fiscal policy realization. Comparative analysis and other approaches were used for this. The author offers to consider the positive experience of EU countries in formation of efficient eco taxation model.The article analyses data characterizing eco tax incomes of EU countries in 2008–2015. The most important aspects of eco taxation realization in EU countries are analyzed, since eco taxes are part of fiscal policy programs aimed to convince society in urgent necessity to make the economy eco-oriented.The article offers complex analysis of environmental pollution and resources taxes structuring. System approach determines the influence of energy and transport taxes on long-term development of eco energy and eco vehicles.Eco taxation partially depends on proper administration which includes determination of contamination level, tax fees, and their ability to react quickly on ecological and economic changes.Eco tax must correspond to the level of environmental impact. Eco tax incomes are used with different purposes, but compensation of tax incentives are their primary function. Compensation of tax incentives is used to conduct eco tax reform.The key element of stable development of European countries is realization of innovative ecological policy, economic policy, and eco labor tax reform, all directed on environmental protection.
Keywords: eco taxes, fiscal policy, transportation tax, pollution taxes, GDP data, rational resource usage, no-waste production, ecologization of economy.